International legal conventions as an instrument for preventing environmental risks - E. I. Mayorova (Вестник университета)
The participation of the Russian Federation in international environmental conventions and agreements as the successor of the USSR and as a new subject of the international law of the XXth century is considered. Environmental problems arise due to the excessive anthropogenic impact on nature. Rational use of natural resources requires the development and purposeful application of environmental and legal instruments for the protection of the natural objects and systems that are not included into the jurisdiction of individual countries and are not the national heritage of a particular state. The efficiency of the norms of the international environmental law is low since they come into conflict with the economic interests of states. Nature continues to be considered as the basis of the economy, and participation in international agreements means restrictions on certain economic activities, therefore, a number of countries do not ratify international environmental conventions for economic reasons, neglecting environmental consequences. Another reason for the refusal of ratification is the desire to hide from the public information about the deterioration of the environment, which is a violation of the interests of civil society and a risk to human health.